Corporate governance and banking performance: a comparative study between private and state banking sector in sri lanka - Ajanthan, A.; Balaputhiran, S.; Nimalathasan, B. (University of Jaffna, 2013)
The main objectives of this study are to find out the relationship between corporate governance and banking performance and also find out the impact of corporate governance on banking performance. This study focused on four aspects of corporate governance namely; Board Size (BS), Board Diversity (BD), Outside Directors Percentage (OSDP) & Board Meeting Frequency (BMF). Banking performance has been measured through Return on Equity (ROE) and Return on Assets (ROA). The results revealed that all variables of corporate governance are positively correlated with ROE in state banks as well as, in private banks except BD and BMF other variables have strong negative relation with ROE, which is significant at 5percent level of significance. Similarly, except BMF other variables have negative relationship with ROA in state banks. Private Banks also show same relation except the variable BD. BD have strong negative relationship with ROA in state banks which is significant at 5 percent level of significance, but in private banks; positive relationship is denoted by BD which is not significant. Further corporate governance has a moderate impact on performance of both private and state banks.
Keywords: Corporate governance; Banking sector; Banking performance